How locally owned and sustainable are victims’ groups in postconflict and transitional settings?: reflections from northern Uganda - Schulz, Philipp (International journal of transitional justice, 2023)
Victims’ groups in postconflict settings have gained increasing attention in transitional justice scholarship and programming, as entry points for victims to engage with external transitional justice mechanisms, or as vehicles to facilitate healing, recovery or justice making on the micro level. These groups are often presented in terms of local ownership, victims’ participation and self-reliance. Based on work in Uganda, I have previously argued that victims’ groups constitute locally owned and sustainable resources that can facilitate a sense of justice for survivors on their own terms. Yet, based on recent field research observations, I have to ask myself: how locally owned and sustainable are these groups really? Due to a lack of donor support and external resources, the group that I worked with has become inactive since 2020. In this Note, I explore the reasons for and implications of this, with the intention of critically engaging with some of my previous arguments.